The Laser as a STEAM Engine - Korae, Eva (My University, 2025)
This poster is based on a photo book by Eva Korae, which is essentially a record of experiments performed on a CO2 laser cutter from the maker’s perspective. It sprung from an unfulfilled need for creative visual stimuli regarding the prospects of laser cutting technology. While popular publications efficiently explain the basics of operating and cutting, they appear to leave the more creative possibilities unexplored. While the possibilities of CO2 lasers offer the capability of working with a wide variety of materials, users appear reluctant to try something they have not seen used before and this publication aims to fill this gap. Therefore the research question lies mainly on visually complementing mainstream information found in books, online discussion groups and commercial laser websites through explaining how to test for material suitability and recording the process of more than 100 materials. The results presented contribute to laser user confidence in performing unusual experimentations, while acting as a behind the scenes demonstration of published, internationally recognized creative outcomes.
Keywords: Laser Engraving, Laser Cutting, Laser Engineering, Creative Laser, STEAM Education